Numerical study on influence of wind on thermal performance of a solid particle solar receiver - Li, Zhenzhong; Wang, Bowen; Xu, Liangjin; Wei, Jinjia; Bu, Shanshan; Chen, Deqi (Frontiers in Energy Research, 2022)
The effects of wind speed and wind attacking angle on the thermal performance of a solid particle solar receiver (SPSR) are studied by numerical simulation. In addition, the effect of aerowindow on the efficiency of the solar receiver is also explored. The results show that under different wind speeds and attack angles, wind can differently prevent hot air from flowing out and carry cold air into the solar receiver. These two effects compete with each other, resulting in the complex influence law of wind on receiver efficiency. Generally, the increasing wind speed will eventually lead to a negative effect on the thermal efficiency of the receiver. At the incident radiation aperture, the aerowindow formed by the air nozzle can effectively reduce convection heat loss and significantly improve the receiver efficiency. Under the simulation conditions of the present study, there is an optimal air jet velocity to maximize the protection effect of the aerowindow. The heat receiver efficiency increases from 41.7 to 58.2% when the wind is 2.5 m/s and the wind attacking angle is 135°. In the analysis of the energy balance inside the solar receiver, the proportion of radiation heat loss is about one-third, and it is not affected by the aerowindow. Thus, reducing radiation heat loss is very important for further improving the receiver’s efficiency of SPSR.